2017
DOI: 10.1371/journal.pone.0184619
|View full text |Cite
|
Sign up to set email alerts
|

Alkylation induced cerebellar degeneration dependent on Aag and Parp1 does not occur via previously established cell death mechanisms

Abstract: Alkylating agents are ubiquitous in our internal and external environments, causing DNA damage that contributes to mutations and cell death that can result in aging, tissue degeneration and cancer. Repair of methylated DNA bases occurs primarily through the base excision repair (BER) pathway, a multi-enzyme pathway initiated by the alkyladenine DNA glycosylase (Aag, also known as Mpg). Previous work demonstrated that mice treated with the alkylating agent methyl methanesulfonate (MMS) undergo cerebellar degene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 67 publications
(96 reference statements)
3
9
0
Order By: Relevance
“…The results of these experiments are consistent with previous studies showing reduced toxicity from 3MeA relative to BER intermediates (Allocca et al, 2019; Calvo et al, 2013; Ebrahimkhani et al, 2014; Kisby et al, 2009; Margulies et al, 2017; Meira et al, 2009; Sobol et al, 2003). In fact, knockout of Aag has been shown to protect against alkylation-induced toxicity and degeneration in the retina and cerebellum (Allocca et al, 2019; Calvo et al, 2013; Margulies et al, 2017; Meira et al, 2009), and overexpression of Aag sensitizes cells to alkylation-induced toxicity (Hendricks et al, 2002; Ibeanu et al, 1992). In terms of cancer, Aag −/− mice have been found to be more susceptible to exposure-induced mutations and tumors in the colon (Calvo et al, 2012; Fahrer et al, 2015; Meira et al, 2008; Wirtz et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results of these experiments are consistent with previous studies showing reduced toxicity from 3MeA relative to BER intermediates (Allocca et al, 2019; Calvo et al, 2013; Ebrahimkhani et al, 2014; Kisby et al, 2009; Margulies et al, 2017; Meira et al, 2009; Sobol et al, 2003). In fact, knockout of Aag has been shown to protect against alkylation-induced toxicity and degeneration in the retina and cerebellum (Allocca et al, 2019; Calvo et al, 2013; Margulies et al, 2017; Meira et al, 2009), and overexpression of Aag sensitizes cells to alkylation-induced toxicity (Hendricks et al, 2002; Ibeanu et al, 1992). In terms of cancer, Aag −/− mice have been found to be more susceptible to exposure-induced mutations and tumors in the colon (Calvo et al, 2012; Fahrer et al, 2015; Meira et al, 2008; Wirtz et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…PARP-1 stimulates repair of SSBs by polymerizing ADP-ribose from NAD+, so an excess of DNA damage causes NAD+ depletion and a form of programmed necrotic cell death termed parthanatos (Xu et al, 2006; Yu et al, 2002; Zhao et al, 2018). We have previously shown that AagTg mice experience elevated cytotoxicity and tissue degeneration from DNA alkylating treatments in the cerebellum, retina, spleen, thymus, bone marrow, and pancreas (Allocca et al, 2017; Allocca et al, 2019; Calvo et al, 2013; Margulies et al, 2017), and that this is often dependent on PARP-1. Indeed, histopathology of NDMA-treated AagTg livers showed significantly elevated necrosis over that of WT and Aag −/− livers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to stress that AAG-dependent alkylation-induced cell death is cell-type specific (29,64). We observed alkylation-induced cell death only in the PR cells but not in other retinal cell types.…”
Section: Discussionmentioning
confidence: 61%